Perubahan Misi Budaya Merantau: Studi Perantau Etnik Batak Di Kawasan Industri Cikarang, Bekasi - Hidayat Hidayat (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2023)
The cultural values of Dalihan Na Tolu, religion, hagabeon, hasangapon, hamoraon, hamajuon are normative values, continue to be preserved in nature bona pasogit and become a cultural mission in the Toba Batak ethnic migration activities. Factors that influence the activities of migrating Toba Batak ethnicity are closely related to push-pull factors that combine with the socio-cultural conditions of the migrants' hometowns. The process of migrating them is distinguished by permanent and non-permanent, their arrival to the destination of migrating is direct and indirect. Considering that the destination for migrating is an industrial and business area, the cultural mission of migrating is not meant to halului anak, halului tano and build the Batak harajoan.” The arrival of migrants to the destination area is to earn a living and survive because the destination area for migrating is the Cikarang industrial area which has developed into one of the landscapes of the largest business empire in Indonesia.